SWOT ANALYSIS FOR STARTUP BUSINESSES - Ananda, Rosmita Dewi; Bahiroh, Eloh (Management Science Research Journal, 2023)
Companies must always pay attention to market conditions and compete more fiercely when determining strategy in the face of growing global competition. One method for determining each force's level of competitiveness is through competitive strategy, SWOT analysis effectively can help determine a company's competitive strategy by identifying the company's strengths, weaknesses, opportunities, and threats to its continued existence. The question that needs to be answered by this study is, "Are SWOT analysis the right strategy to determine competitive strategies for startup business?". The research method using descriptive analysis with the analyze of qualitative data. Archives or documents are gathered for this study using secondary data.